International Conference on “Foresight Studies on Work in the Knowledge Society“ in Monte de Caparica (FCT-UNL) on 19-20 October 2006 - Woll, Tobias (2008)
On 19 and 20 October 2006, the Research Centre on Enterprise and Work Organisation (IET) organised the first international conference on “Foresight Studies on Work in the Knowledge Society”. It took place at the auditorium of the new Library of FCT-UNL and had the support of the research project “CodeWork@VO” (financed by FCT-MCTES and co-ordinated by INESC, Porto). The conference related to the European research project “Work Organisation and Restructuring in the Knowledge Society” (WORKS), which is financed by the European Commission. The main objective of the conference was to analyse and discuss research findings on the trends of work structures in the knowledge society, and to debate on new work organisation models and new forms of work supported by ICT.